Syntax of Dutch: Adjectives and Adjective Phrases - Broekhuis, Hans (Comprehensive Grammar Resources, 2013)
The Syntax of Dutch will be published in at least seven volumes in the period 2012-2016 and aims at presenting a synthesis of the currently available syntactic knowledge of Dutch. It is primarily concerned with language description and not with linguistic theory, and provides support to all researchers interested in matters relating to the syntax of Dutch, including advanced students of language and linguistics. The volume Adjectives and Adjective Phrases discusses the internal make-up as well as the distribution of adjective phrases. Topics that will be covered include: complementation and modification of adjective phrases; comparative and superlative formation; the attributive, predicative and adverbial uses of adjective phrases. Special attention is paid to the so-called partitive genitive construction and the adverbial use of past/passive participles and infinitives.